Gestão de eventualidades em unidades sanitárias: estratégias para resposta eficaz - Tomás Américo; Maulano Marcos (Revista ft, 2026)
Managing unexpected events in healthcare facilities poses a challenge to the promotion, continuity, and delivery of health services at the required minimum quality level. This study focuses on the management of such events in healthcare facilities, aiming to analyze strategies for prevention, preparedness, and response. It highlights the roles of leadership, efficient resource management, institutional communication, and the development of contingency plans in fostering organizational resilience when facing unexpected events. Methodologically, this is a basic, descriptive study employing a qualitative approach. Data collection relied on a literature review and document analysis of scientific literature, technical standards, and publications from national and international health organizations. The results indicate that implementing contingency plans, strengthening institutional logistics management, providing continuous staff training, ensuring effective communication, and practicing adaptive leadership are decisive factors in mitigating the impact of unexpected events and ensuring the continuity of essential health services. The study concludes that strengthening institutional capacity to prevent, respond to, and recover from adverse situations is a strategic element for enhancing the resilience of healthcare facilities and improving the quality of care provided to the population.